Tasks, Talkers, and the Perceptual Learning of Time-Compressed Speech. Issue 1 (2nd April 2020) - Tarabeih - Ghanayim, Maram; Lavner, Yizhar; Banai, Karen
ABSTRACT: Many auditory skills (e.g., the recognition of perceptually difficult speech) improve with practice, but only limited transfer of this learning to untrained materials was observed in previous studies. Here, we asked whether the type of practice (semantic or accent judgment) and talker variability (defined as the number of different talkers encountered during practice, two or six), influenced the perceptual learning of time-compressed speech and its transfer to unpracticed materials. Four groups of participants trained on the four task/talker variability combinations, and their pre- and post-training recognition of time-compressed speech was compared to that of a group of untrained participants (n = 14–16 participants/group). Across groups, training led to substantial learning of the trained tokens and to transfer to new talkers producing previously encountered sentences (compared to the untrained control group). However, neither type of training had a significant effect on the recognition of new sentences, even for familiar talkers. Semantic training yielded more learning and better retention of learning over a 2-week interval than accent training. The number of talkers had only marginal effects. These results suggest that learning of time-compressed speech is robust and only partially task-specific, but its transfer to untrained tokens following brief practice is limited. In contrast to other types of speech training, here exposure to a variety of talkers during training did not contribute to the transfer of learning to new materials.